The biological function and prognostic significance of ferroptosis-related genes in clear cell renal cell carcinoma - Ye, Huizhen; Wu, Xiwen; Liang, Gehao (Frontiers in Pharmacology, 2025)
BackgroundFerroptosis-related genes are essential in cancer development. However, the specific roles of ferroptosis-related genes in clear cell renal cell carcinoma (ccRCC) remain largely unexplored. This study aims to elucidate the biological functions and potential therapeutic implications of ferroptosis-related genes in ccRCC.MethodsA model integrating the Cancer Genome Atlas (TCGA) database and the GEO dataset was established based on ferroptosis-related genes and clinical data. To determine the proliferative function of ferroptosis-related genes in ccRCC cells, CCK-8 kit assays and colony formation experiments were conducted. Additionally, wound-healing experiments were performed to evaluate the migratory capabilities of these cells.ResultsWe identified eight ferroptosis-related genes that are significantly associated with the prognosis of ccRCC patients. The expression levels of these genes exhibited marked differences between tumor tissues and normal tissues, and they were shown to influence both the proliferation and metastasis of ccRCC cells. Subsequently, a model combining ferroptosis-related genes model constructed with gene data and clinical characteristics was constructed, and classified the patients into high- and low-risk groups. The area under the curve (AUC) for this model in diagnosing ccRCC was 0.937. In terms of survival prediction, the AUC values were 0.875, 0.818, and 0.790 at 1, 3, and 5 years, respectively. Notably, high-risk patients exhibited significantly poorer survival outcomes compared to those in the low-risk group. Furthermore, high-risk individuals demonstrated elevated expression of immune checkpoint genes and enhanced antitumor immunity, suggesting that these patients may benefit from immunotherapy.ConclusionFerroptosis-related genes play a critical role in the biological functions of ccRCC cells. Our prognostic model has the potential to be applied in predicting patient outcomes and assessing antitumor immunity in ccRCC.